Association of P-wave characteristics with long-standing atrial high rate episodes (AHREs) following pacemaker implantation - Wei Zhu; Renlin Yin; Liting Zhi; Xingmei Huang; Lili Mei; Peng Yang; Cao Zou (BMC Cardiovascular Disorders)
Abstract Background The study is aimed at identifying the risk factors for long-standing atrial high rate episodes(AHREs) following pacemaker implantation. Methods A retrospective study was conducted on 180 patients who underwent pacemaker implantation between 01 Jan 2021 and 31 Dec 2021. Patients were divided into AHRE group(70 cases) and no AHRE group(110 cases) based on pacemaker interrogation results. Patients in AHRE group were divided into two groups: AHRE < 24 h group(36 cases) and AHRE ≥ 24 h group (34 cases). Basic clinical data, programming parameters, P-wave terminal force in V1(PTF V1), P-wave duration, P-wave dispersion(PWD), interatrial block (IAB), low P-wave voltage in lead I(low-PVLI), P-wave peak time(PWPT) and morphology-voltage-P wave(MVP) score of sinus and paced P wave were compared. Results The AHRE group had higher cumulative percentages of atrial pacing(AP%) and ventricular pacing(VP%). PWPT of sinus and paced P wave, MVP score of paced P wave and PWD of sinus P wave were longer in AHRE group (P < 0.05). High VP% was an independent risk factor for AHRE(P = 0.019). AHRE ≥ 24 h group had more patients with sick sinus syndrome(SSS) (P = 0.014) and advanced IAB (P < 0.05). High MVP score, long PWPT and P-wave duration of paced P wave were observed in AHRE ≥ 24 h group, with high MVP score and long PWPT as independent risk factors for long-standing AHRE(P = 0.006 and P = 0.007). Conclusion High VP% was an independent risk factor for AHREs. Increased MVP score and PWPT of paced P wave may associate with long-standing atrial high rate episodes.